(untitled) (HISKIA : Jurnal Ilmu Kimia & Pendidikan Kimia, 2025)
Acid–base indicators, also known as pH indicators, are chemical substances that exhibit distinct color changes in acidic or basic solutions. Commonly used indicators in chemical analysis are typically synthetic, toxic, expensive, and environmentally unfriendly. Red cabbage (Brassica oleracea L.) is a vegetable rich in anthocyanins, natural pigments responsible for plant coloration, which are sensitive to pH changes. This property makes them a potential source of eco-friendly, inexpensive, and non-toxic natural pH indicators. This study aimed to examine the color characteristics of Red Cabbage Extract (RCE) in solutions with pH values ranging from 1 to. The results showed that RCE had a deep red color in its concentrated form, bright pink at pH 1–2, pale pink at pH 3–6, pale purple at pH 7, pale blue at pH 8–10, bluish-green at pH 11–12, yellowish-green at pH 13, and yellow at pH 14. RCE also exhibited clear and distinguishable color changes when used to identify various household samples. These findings suggest that RCE is an effective, low-cost, and eco-friendly natural pH indicator that supports the principles of green chemistry.